The Use of Tanniferous Plants to Control Infestations of Haemonchus contortus Parasites in Meat Goats - Tyrell Kahan; Sally Williams; Ray Mobley; Ikechukwu Ezenwa; Eric Peterson (EDIS, 2008)
AN199, a 6-page fact sheet bu Tyrell Kahan, Sally Williams, Ray Mobley, Ikechukwu Ezenwa, and Eric Peterson, describes the use of tanniferous plants to control internal parasites in meat goats. Includes references. Published by the UF Department of Animal Science, March 2008.